2005
DOI: 10.1007/s11745-005-1475-0
|View full text |Cite
|
Sign up to set email alerts
|

Intake of conjugated eicosapentaenoic acid suppresses lipid accumulation in liver and epididymal adipose tissue in rats

Abstract: It has been reported that consumption of CLA and EPA alters lipid metabolism. CLA contains conjugated double bonds, and EPA is an n-3 PUFA. Based on the possibility that a molecule with both of these structures might have interesting physiological effects, we prepared conjugated FA from EPA by alkaline isomerization and examined the effects of the conjugated EPA (CEPA) on lipid metabolism in rats. Rats were fed by oral gavage every day for 4 wk with 200 mg of FA including linoleic acid, EPA, CLA, or CEPA. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Previous studies described that EPA consumption increases the physiological activity of liver and adipose tissue fatty acid oxidation [35,48]. This effect was assumed in our study because of the significant rise found in serum ketone bodies under both high-fat-diet intake [49] and EPA ethyl ester treatment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies described that EPA consumption increases the physiological activity of liver and adipose tissue fatty acid oxidation [35,48]. This effect was assumed in our study because of the significant rise found in serum ketone bodies under both high-fat-diet intake [49] and EPA ethyl ester treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Numerous studies have shown that ω-3 fatty acids, especially EPA, reduced plasma lipid levels in human and experimental animal models [5,34], mainly through changes in fatty acid synthesis and β-oxidation pathways [8,35]. For this purpose, the aim of the present study was to determine the mechanisms through which EPA ethyl ester improves lipid metabolism in an experimental animal model of obesity induced by high-fat (cafeteria) diet.…”
Section: Discussionmentioning
confidence: 95%
“…The lipid compositions in serum and liver were measured as described previously (11,12). Triacylglycerol (TG) and total cholesterol (TC) levels in serum and liver, and phospholipid (PL), non-esterified acid (NEFA) and glucose levels in serum were measured using commercial enzyme kits (Wako Pure Chemical Industries, Ltd., Osaka, Japan) Fig.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…The lipid compositions in the liver and plasma were measured as described previously (Tsuzuki et al 2005;Tsuzuki et al 2006). Triacylglycerol (TG) and total cholesterol (TC) levels in plasma and liver, and phospholipid (PL), free fatty acid (FFA), and glucose levels in plasma were measured using commercial enzyme kits (Wako Pure Chemical, Osaka, Japan) according to the manufacturer's protocol.…”
Section: Biochemical Analyses In Plasma and Livermentioning
confidence: 99%